History and development of an isolated outbreak of Asian longhorn beetle Anoplophora glabripennis (Coleoptera: Cerambycidae) in southern England. (19th April 2016) - Straw, Nigel A.; Fielding, Nick J.; Tilbury, Christine; Williams, David T.; Cull, Thomas
Abstract: Asian longhorn beetle Anoplophora glabripennis is a major international quarantine pest that is capable of killing a wide range of broadleaved trees. In 2012, an outbreak of A. glabripennis was discovered at Paddock Wood in southern England, which prompted an eradication programme and research to determine when the population had established, as well as how quickly it was spreading. Tree ring analysis of infested stems and branches showed that the first A. glabripennis adult emerged in 2003 and that the beetle had been present for approximately 10 years before it was discovered. However, the population had increased relatively slowly and, even though it could be shown that some beetles travelled 96–203 m to lay eggs in new trees, the population as a whole had not spread further than 234 m. Survival rates of larvae were similar to rates observed in other A. glabripennis populations, although failure at the egg‐laying stage and adult mortality at or before emergence were higher than recorded elsewhere. A combination of factors appears to have allowed A. glabripennis to establish at Paddock Wood: the presence of a highly susceptible host (sycamore), multiple introductions of adult beetles over several years, and a run of warmer than average summers at the time of the initial colonization.